Assessing the Knowledge of Radiology Staff on the Impact of Radiation Exposure and the Importance of Shielding for Patient Protection in Saudi Arabia - Leen Al-Shahrani; Manar Dhafer Al-Amri; Rimas Sultan Al Hufayyan; Ahlam Ahmad Al Qahtani; Taif Khalid Al-Shahrani (International Journal of Advanced Humanities Research)
The growing reliance on radiological imaging for medical diagnosis and treatment has increased the potential risks associated with radiation exposure for both patients and healthcare professionals. In Saudi Arabia, ensuring that radiology staff are adequately knowledgeable about the risks of radiation exposure and the protective measures that can be implemented, such as shielding, is critical for enhancing patient safety. This study aims to evaluate the awareness and understanding of radiology staff in Saudi Arabia regarding radiation risks and the importance of shielding in mitigating these risks. The results indicate that while most radiology professionals are familiar with radiation safety protocols, knowledge gaps remain, particularly concerning newer technologies and best practices for shielding. Recommendations are made to improve ongoing training and raise awareness of patient protection measures.